The release of toxic oligomers from α-synuclein fibrils induces dysfunction in neuronal cells - Roberta Cascella (Nature Portfolio, 2021)
The self-assembly of α-synuclein (αS) is a pathological feature of Parkinson’s disease. The αS species responsible for neuronal damage are not well characterized. Here, the authors show that αS fibrils release soluble prefibrillar oligomeric species responsible for neurotoxicity in vitro.